Improvement on the CO2 corrosion prediction via considering the corrosion product performance. (June 2023) - Wang, Cailin; Xu, Xiusai; Liu, Cuiwei; Luo, Xiaoming; Hu, Qihui; Zhang, Rui; Guo, Hongda; Luo, Xia; Hua, Yong; Li, Yuxing
Abstract: A mechanistic model for general CO2 corrosion of carbon steel with protective iron carbonate (FeCO3 ) scales in the temperature range between 30 ∼ 90 °C, and CO2 partial pressure 0.5 ∼ 3.0 MPa was developed. The mathematical distributions of the thickness and porosity of FeCO3 scales were determined by X-ray micro-computed tomography (µCT) and incorporated into the model. The flux profiles of species under the µCT measured scale thickness and porosity were demonstrated. Moreover, the coupling effects of thickness and porosity on the protectiveness of the corrosion product scales were analysed and the effects of pore distribution were revealed. Highlights: A CO2 corrosion model with FeCO3 protection in high-PT environments was developed. Thickness and porosity measured by µCT were incorporated into corrosion model. Coupling effects of thickness and porosity on scale protectiveness were discussed. Effects of pore distribution on scale protection performance were revealed.